Pengaruh Sistem Pembelajaran Daring Terhadap Minat Belajar Mahasiswa Program Studi Pendidikan Geografi STKIP Kie Raha Pada Masa Pandemi Covid 19 - Darling Surya Alnursa; Syahril Lukman; Irwan Abdullah (Peneliti.net, 2022)
This study aims to determine the effect of the online learning system on interest in learning at STKIP Kie Raha, especially in students of the Geography Education study program. The technique of collecting data in this research is through observation techniques, literature review, and distributing questionnaires. The instrument in this study includes the independent variable (X) which is an online learning system and the dependent variable which is (Y) is the student's interest in learning. Testing of the instrument was carried out with normality test (Pearson Product Moment correlation), and reliability test (Cronbach's Alpha coefficient). Data analysis was carried out by simple linear regression, and to see the strength of the relationship between two variables, the Spearman Rank correlation test was used. The results of this study indicate that the online learning system can have an influence on student interest in learning. However, the effect here shows a negative relationship between the two variables. This can be seen from the negative regression coefficient value. It can be concluded that if online lectures increase, students' interest in learning decreases.